Peran Audit Internal Dalam Upaya Pencegahan dan Pengendalian Terjadinya Kecurangan (Fraud) Di Perusahaan - Irma Laelani Muflihah; Ersi Sisdianto (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This research aims to determine the role of internal audit in efforts to prevent and control fraud in companies. The research method uses qualitative literature studies with research sources coming from relevant journals. Technology has made all aspects of life easier now, including auditing and accounting. An accountant is required to be able to keep up with current developments. One of the efforts that can be done is by mastering various accounting software. Internal auditors can carry out evaluations in the form of assessments and tests related to the internal control system implemented by a company. It can be concluded from the results of this research that with fraud becoming more diverse, the solution to this problem is that companies must take action by strengthening internal supervision supported by advances in information technology as well. Internal audit plays a major role in controlling fraud.